Effect of P2Y12 inhibitors on inflammation and immunity - Thomas, Mark R.; Storey, Robert F. (Thrombosis and Haemostasis, 2015)
Platelet P2Y12 inhibitors form a major part of the treatment strategy for patients with acute coronary syndromes (ACS) due to the importance of the platelet P2Y12 receptor in mediating the pathophysiology of arterial thrombosis. It has been increasingly recognised that platelets also have a critical role in inflammation and immune responses. P2Y12 inhibitors reduce platelet release of pro-inflammatory α-granule contents and the formation of pro-inflammatory platelet-leukocyte aggregates. These are important mediators of inflammation in a variety of different contexts. Clinical evidence shows that P2Y12 inhibition by clopidogrel is associated with a reduction in platelet-related mediators of inflammation, such as soluble P-selectin and CD40L, following atherothrombosis. Clopidogrel in addition to aspirin, compared to aspirin alone, also reduces markers of systemic inflammation such as tumour necrosis factor (TNF) α and C-reactive protein (CRP) following ACS. The more potent thienopyridine P2Y12 inhibitor, prasugrel, has been shown to decrease platelet P-selectin expression and platelet-leukocyte aggregate formation compared to clopidogrel. The PLATO study suggested that the novel P2Y12 inhibitor ticagrelor might improve clinical outcomes from pulmonary infections and sepsis compared to clopidogrel in patients with ACS. Ticagrelor is a more potent P2Y12 inhibitor than clopidogrel and also inhibits cellular adenosine uptake via equilibrative nucleoside transporter (ENT) 1, whereas clopidogrel does not. Further examination of the involvement of these mechanisms in inflammation and immunity is therefore warranted.
Keywords: Platelets; P2Y12 inhibitors; antiplatelet medications; inflammation; infection